Prolonged Heterogeneous Liver Enhancement on Contrast-Enhanced Ultrasound - Cui, X. W.; Ignee, A.; Hocke, M.; Seitz, K.; Schrade, G.; Dietrich, C. F. (Ultraschall in der Medizin - European Journal of Ultrasound, 2014)
Introduction: Prolonged heterogeneous liver enhancement (PHLE) is a rare phenomenon that is similar to the ultrasound findings of portal venous gas. The purpose of this report is to describe the phenomenon of PHLE after the injection of the ultrasound contrast agent SonoVue®.Patients and Methods: From 2000 to 2013, 13 patients with PHLE (“cloudy”, “wool-like”) after bolus injection of SonoVue® were observed. The height, weight, and body mass index (BMI) of the patients, and the number of injections were analyzed. In addition, the literature was reviewed.Results: The phenomenon occurred as early as 2 minutes after bolus contrast administration and lasted up to 5 hours on both B-mode and contrast-specific ultrasound. 8/13 (62 %) patients received two or more boluses. None of the patients experienced SonoVue®-related side effects or health problems. The phenomenon was not reproducible in 3 patients who received a second SonoVue® injection 24 hours after receiving the first.Conclusion: This phenomenon is more likely to occur in patients who receive high-dose (or multiple) injections of UCA. It may occur as early as 2 minutes after contrast administration, and therefore, may affect the evaluation of focal liver lesions in the late phase. This phenomenon should not be misdiagnosed as a pathological finding of the liver.
Keywords: ultrasound; microbubbles; liver; heterogeneous enhancement